Exploring the domestic relationship between mega-events and destination image: The image impact of hosting the 2012 Olympic Games for the city of London. Issue 3 (June 2018) - Kenyon, James Andrew; Bodet, Guillaume
Highlights: London managers and stakeholders aimed leverage the 2012 Olympics to improve the image of the city. London's image contains some stable cognitive and affective image components. However, attitudes towards the city were negatively impacted pre-to-post-event. The image of the 2012 Games improved considerably following the event. There was no evidence of co-branding between the place and event. Abstract: Contemporarily, the hosting of mega-sport-events (MSEs) is one of several strategies used by cities and governments to bring about improvements in a place's image and recognition. With that in mind, the overall aim of this study, underpinned by theoretical-methodological social representation theory, was to evaluate the domestic image impact of hosting the 2012 Summer Olympic Games for the city of London, and in doing so, whether any image-transfer (or co-branding) processes occurred between the place and event. In addition to adding to the emergent body of work aimed at using social representation theory to measure place image, the authors are among the first to employ a matched-sample research approach to measuring the impact of an MSE on the domestic perceptions of the host. Employing an abductive research strategy, a survey was carried out among the domestic English population ( n  = 156) to identify cognitive and affective image components, in the form of social representations, of London as a city (or its place brand), the Olympics as a MSE, and the 2012 Games as a one-off event. The content and the structure of the pre-and post-event social representations were established (using image elements cited by at least 15% of the respondents), analysed (using hierarchical cluster analysis) and then compared (within- and between items) to determine whether any changes or image transfer occurred. The findings of this research reveal that the pre-event concerns regarding the hosting of the London 2012 Olympics and the potential of the event to negatively impact the city's pre-established image, were, to a degree, fulfilled. Conversely, from an event perspective, respondents perceived the Olympics as a somewhat successful enterprise.